Do We Need Moral Facts? - Payton, Jonathan (The Oracle, 2021)
In this article I answer Gilbert Harman’s objection to the possibility of objectivity in the field of ethics, namely, that there is no such thing as a “moral fact.” I analyze the argument using terminology from G. E. Moore’s Principia Ethica and try to apply it to utilitarian moral theory. After demonstrating that utilitarianism does not, in fact, make any appeal to moral facts, I then consider the implications of Harman’s theory for the field of ethics as a whole. I conclude that his argument is based on a misunderstanding of ethics and that values are not to be found in the world, but are to be found in us. I then give some closing remarks about one possibility for the construction of an objective system of ethics which finds its basis in the subject.